A Hydrodynamic Modelling of Atmospheric Escape and Absorption Line of WASP-12b. Issue Volume 14:Issue S345(2019) (August 2018) - Dwivedi, N. K.; Khodachenko, M. L.; Shaikhislamov, I. F.; Berezutsky, A. G.; Miroshnichenko, I. B.; Fossati, L.; Lammer, H.; Sasunov, Y.; Kislyakova, K. G.; Johnstone, C. P.; Güdel, M.
Abstract: Self-Consistent 2D modelling of stellar wind interaction with the upper atmosphere of WASP-12b has been performed. The two case-scenarios of the planetary material escape and interaction with the stellar wind, namely the 'blown by the wind' (without the inclusion of tidal force) and 'captured by the star' (with the tidal force) have been modelled under different stellar XUV radiations and stellar wind parameters. In the first scenario, a shock is formed around the planet, and the planetary mass loss is controlled completely by the stellar radiation energy input. In the second scenario, the mass loss is mainly due to the gravitational interaction effects. The dynamics of MG II and related absorption were modelled with three sets of different stellar wind parameters and XUV flux values.